Increased Depression Affects Hyperglycemia Status in Type II Diabetes Mellitus Patients - Dwi Nur Aini; Menik Kustriyani; Arifianto Arifianto (Media Keperawatan Indonesia, 2019)
Diabetes mellitus is a collection of symptoms that arise in a person caused by an increase in blood glucose levels. Chronic diseases such as type II diabetes mellitus can affect their psychological condition, namely depression. From the preliminary results the researchers compared 5 patients with type II diabetes mellitus in the Mijen health center area, 1 of them experienced fatigue, 4 of them experienced insomnia, were not productive, tired quickly when activity and appetite decreased. The purpose of the study was to determine the relationship between the level of depression with blood sugar levels in patients with type II diabetes mellitus. This type of research uses quantitative non-experiment with cross sectional design. Sampling with purposive sampling technique. Data were collected through questionnaires, analyzed using Sperman rank statistical test with a significant limit of 0.05. In this research shows pearson correlation coefficient rate of 0,524 and ρ =0,000. It show the  significant positive correlation between depression and blood glucose level on diabetic type II patient with the medium corelation level. The results showed that there was a relation between depression with blood glucose  level in diabetes mellitus type II patients.